1985
DOI: 10.1089/hyb.1985.4.243
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibody to a Highly Glycosylated Protein Reacts in Fixed Tissue With Melanoma and Other Tumors

Abstract: A highly glycosylated protein with a molecular weight of 30,000 to 60,000 and a protein core of 20,000 daltons has been identified by antimelanoma monoclonal antibodies. The antigenicity of this melanoma-associated glycoprotein (MAG) was not destroyed in fixed paraffin-embedded melanoma tissue, and was present in malignant cells of cutaneous superficial spreading melanomas in skin (31/33) and in half of all metastatic melanomas examined (5/10). The antigen was not expressed by normal melanocytes. The strong re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1

Year Published

1987
1987
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 18 publications
2
27
1
Order By: Relevance
“…This difference at the mRNA level was confirmed at the protein level by FACS analysis ( Figure 3A). In contrast, two other tetraspanin proteins, CD82 and CD63, that are also reported to correlate with tumor progression [32][33][34][35][36][37][38] did not have any difference in expression between L3055-12 and L3055-33 ( Figure 3A).…”
Section: Cd9-positive Cells Grow Slower and Are More Dependent On Fdcmentioning
confidence: 99%
“…This difference at the mRNA level was confirmed at the protein level by FACS analysis ( Figure 3A). In contrast, two other tetraspanin proteins, CD82 and CD63, that are also reported to correlate with tumor progression [32][33][34][35][36][37][38] did not have any difference in expression between L3055-12 and L3055-33 ( Figure 3A).…”
Section: Cd9-positive Cells Grow Slower and Are More Dependent On Fdcmentioning
confidence: 99%
“…Reduced expression of these molecules is more frequently observed in metastatic tumors than primary sites, and patients with tumors lacking these molecules tend to be at advanced stages and thus show poor survival. Downregulation in CD9 or CD82 is associated with the progression of differentiated carcinomas such as breast Huang et al, 1998;Yang et al, 2000), pancreas (Guo et al, 1996;Sho et al, 1998), colon (Cajot et al, 1997;Lombardi et al, 1999), esophagus (Uchida et al, 1999), and NSCLC (Higashiyama et al, 1995;Adachi et al, 1996Adachi et al, , 1998, whereas CD63 reduction associated with that of melanoma (Atkinson et al, 1985;Hotta et al, 1988). Intriguingly, CD63 expression had no correlation with the spread of NSCLC and pancreatic cancer Sho et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Low CD9 expression correlates with breast cancer metastasis (Miyake et al, 1995). A study of skin-superÂźcial spreading melanomas and metastatic melanomas showed that CD63(ME491) expression associates with early stages of melanoma progression and reduced expression in advanced stages of melanoma (Atkinson et al, 1985).…”
Section: Introductionmentioning
confidence: 99%